COMPARISON OF PAI AND PAK: AN OVERVIEW OF VALUES OF MULTICULTURAL EDUCATION - Ali Murfi (Ta'dib: Jurnal Pendidikan Islam, 2015)
This research to reveal comparative Islamic Education (PAI) with Christian Education (PAK) through a textbook’s lesson in terms of content values of multicultural education. The comparative’s analysis includes three aspects, differences, similarities, and common platform. The results showed that substance of values of multicultural education contained in the textbooks have much in similarities which eventually became common platform both than the differences that exist, so that PAI and PAK should move bind themselves to each other in one joint effort to raise the noble values of multicultural, where both scientific traditions stand firm through efforts integration and comprehension charge of teaching materials.